THE REDUCING OF ORGANIC LOADING AND PHOSPHATE (PO4) IN DOMESTIC WASTEWATER TREATMENT BY CONSTRUCTED WETLAND SYSTEM USING CANNA INDICA AND CYPERUS ALTERNIFOLIUS - Rendi Yopi Trifando; Haryati Bawole Sutanto; Guruh Prihatmo (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2022)
The domestic wastewater is mostly produced in settlement areas and usually directly discharged into the environment. Its high organic matter and nutrients will pollute the environment. As an alternative, one of the good wastewater treatment systems is the Sub Surface Flow Constructed Wetland. This system has some advantages such as easy implementation, low cost, and doesn’t need a large area. The aim of this study is to determine the efficiency of Canna indica and Cyperus alternifolius to reduce organic matter and phosphate. This study is an experimental study with two treatments (T1: SSF CW with Canna indica; T2: SSF CW with Cyperus alternifolius). The SSF CW system contains gravels those diameters are 3-5 cm, 1-3 cm, and <1 cm, as well as paddy soil as media with HRT of 3 days. The parameters measured included temperature, BOD, DO, PO4, and pH. Based on this study, it can be concluded that the higher removal efficiency of organic matter is shown by the CW SSF system with Cyperus alternifolius. It is 48,86% in T2 and 42,69% in T1. While the removal efficiency of phosphate in T1 and T2 are 65,70% and 67,21% respectively.